+0  
 
-1
47
2
avatar

Define g by g(x)=5x-4. If \(g(x)=f^{-1}(x)-3\) and \(f^{-1}(x)\) is the inverse of the function f(x)=ax+b, find 5a+5b.

 

I don't know how to do this.

 May 10, 2020
 #1
avatar+20906 
+1

First:  given  f(x)  =  ax + b,  find  f-1(x):

           1)  let  y  =  f(x)                  --->     y  =  ax + b

           2)  interchange x and y      --->     x  =  ay + b

           3)  solve for y:                    --->     x - b  =  ay     --->     y  =  (x - b) / a

           4)  exchange f-1(x) for y     --->     f-1(x)  =  (x - b)/a

 

Since  g(x)  =  f-1(x)  - 3    --->     g(x)  =  (x - b)/a - 3

Since  g(x)  =  5x - 4       --->     5x - 4  =  (x - b)/a - 3

Rewriting:                                  5x - 4  =  x/a - b/a - 3

 

Setting the x-terms equal to each other:  5x  =  x/a

                                                     --->     5ax  =  x

                                                     --->       5a  =  1

                                                     --->         a  =  1/5

 

Setting the numbers equal to each other:  -4  =  -b/a - 3

                                                     --->        -1  =  -b/a

                                                     --->        -1a  =  -b

                                                     --->           a  =  b

                                                     --->           b  =  1/5

 May 10, 2020
 #2
avatar
+1

Thank you!

Guest May 10, 2020

17 Online Users

avatar